2018
DOI: 10.2478/s11756-018-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental diversity of hunting complexes in the Lublin region on ontogenetic quality indicators in roe deer (Capreolus capreolus)

Abstract: Populations of game are not confined to single ecosystems but function within higher-order units, e.g. ecological landscape. The basis for the establishment of the hunting complexes was the assumption that the existing game hunting grounds, i.e. the basic units implementing game management, are too small and do not cover the natural areas inhabited by game populations. Roe deer are flexible species and easily adapt to various site conditions, so they inhabit many different habitats, from large forest complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Research on energy reserves in cervids in Poland has been conducted in deer [Bobek et al 1990, Okarma 1991, Dzięciołowski et al 1996, Drozd and Piwniuk 2000 and roe deer [Drozd and Gruszecki 2000, Karpiński et al 2008, Czyżowski et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Research on energy reserves in cervids in Poland has been conducted in deer [Bobek et al 1990, Okarma 1991, Dzięciołowski et al 1996, Drozd and Piwniuk 2000 and roe deer [Drozd and Gruszecki 2000, Karpiński et al 2008, Czyżowski et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy animals discard antlers during late autumn, after which the growth of new antlers begins immediately during winter (Sempéré et al, 1998). Growth and rejection of antlers is a very complex process, which comes as a result of achieving the balance between hormonal factors (Price and Allen, 2004), genetic factors (Scribner et al, 1989), environmental factorsnutrition, length of light period, conditions in the habitat and population density (Bán and Fodor, 1982;Pélabon and Breukelen, 1998;Czyżowski et al, 2018). Hormonal growth control is a result of the balance of testosterone, growth hormone (GH), insulin-like growth factor I (IGF-I) and thyroid hormones, as well as parathyroid and adrenal hormones that play a role in controlling the metabolism of minerals (Bartos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These individuals have faster body development and are of better body condition, so the morpho-metric elements and overall trophy score sooner culminate compared to roe deer from forest habitats (Pételis and Brazaitis, 2003;Janiszewski et al, 2009). Research of Czyżowski et al (2018) conducted on 518 European roe deer animals (Capreolus capreolus L.) aged 4 to 7 years, originating from the hunting complexes in Lublin (Poland) showed that individuals from areas with denser forest cover have lower mean values of ontogenetic quality parameters (carcass weight, renal fat index, breast circumference, antler weight) compared to roe deer from typical agricultural areas.…”
Section: Introductionmentioning
confidence: 99%